Molecular detection and characterization of Cryptosporidium spp., Giardia duodenalis, and Enterocytozoon bieneusi infections in dromedary camels (Camelus dromedaries) in Egypt - Elmahallawy, Ehab Kotb; Köster, Pamela C.; Dashti, Alejandro; Alghamdi, Samia Qasem; Saleh, Amira; Gareh, Ahmed; Alrashdi, Barakat M.; Hernández-Castro, Carolina; Bailo, Begoña; Lokman, Maha S.; Hassanen, Eman A. A.; González-Barrio, David; et al. (Frontiers in Veterinary Science, 2023)
Few studies have investigated the occurrence of microeukaryotic gut parasites in dromedary camels in Egypt, and the majority of these investigations are based on microscopic analysis of fecal material. Herein, we assessed the occurrence, molecular diversity, and zoonotic potential of protozoan (Cryptosporidium spp., Giardia duodenalis) and microsporidian (Enterocystozoon bieneusi) pathogens in individual fecal samples (n = 102) of dromedary camels with (n = 26) and without (n = 76) diarrhea from Aswan Governorate, Upper Egypt. Other factors possibly associated with an increased risk of infection (geographical origin, sex, age, and physical condition) were also analyzed. The SSU rRNA or ITS genes were targeted by molecular (PCR and Sanger sequencing) techniques for pathogen detection and species identification. The most abundant species detected was G. duodenalis (3.9%, 4/102; 95% CI: 1.1–9.7), followed by Cryptosporidium spp. (2.9%, 3/102; 95% CI: 0.6–8.4). All samples tested negative for the presence of E. bieneusi. Sequence analysis data confirmed the presence of zoonotic C. parvum (66.7%, 2/3) and cattle-adapted C. bovis (33.3%, 1/3). These Cryptosporidium isolates, as well as the four Giardia-positive isolates, were unable to be amplified at adequate genotyping markers (Cryptosporidium: gp60; Giardia: gdh, bg, tpi). Camels younger than 2-year-old were significantly and more likely to harbor Cryptosporidium infections. This connection was not statistically significant, despite the fact that two of the three cryptosporidiosis cases were detected in camels with diarrhea. The spread of G. duodenalis infections was unaffected by any risk variables studied. This is the first report of C. parvum and C. bovis in Egyptian camels. The finding of zoonotic C. parvum has public health implications since camels may function as sources of oocyst pollution in the environment and potentially infect livestock and humans. Although preliminary, this study provides useful baseline data on the epidemiology of diarrhea-causing microeukaryotic parasites in Egypt. Further research is required to confirm and expand our findings in other animal populations and geographical regions of the country.